Study of the effect of Adding Green Tea (Camellia sinensis) Extract on the Propoerties of Biodegradable Film from κ-Carrageenan - Nurlaida; Saadatul Husna; Andi Wahyu Trifany (EKSAKTA: Journal of Sciences and Data Analysis, 2024)
Carrageenan is a polysaccharide widely used as a material in the packaging industry in search of plastic replacement. κ-Carrageenan contains the lowest amount of sulfat group among other types of carrageenan which makes it the most hydrophobic one. Hence, the most suitable kind for this particular purpose. This research combined commercially available of both κ-Carrageenan and green tea extract (gte) to create a biodegradable film and then to study its characteristics. The concentration of gte was made as 0 µg/mL, 5 µg/mL, and 1 µg/mL while the concentration of κ-Carrageenan and glycerol remained constant. Incorporation of gte produces in darker, colorless film. While there is no effect of gte addition in water content observed, the higher concentration of gte will create a thinner film and lower level of water vapor permeability (WVP). An additional study of the mechanical properties of κ-Carrageenan/gte film indicated a direct proportion between the concentration of gte and tensile strength of the film. Meanwhile, there is no sign of correlation between gte concentration and elongation at break. SEM study displayed a more compact surface with smaller pores when the concentration of gte is increased